Piloting the affordable medicines facility-malaria: what will success look like? - Gavin Yamey; Marco Schäferhoff; Dominic Montagu
The Affordable Medicines Facility-malaria is an innovative financing mechanism, managed by the Global Fund to Fight AIDS, Tuberculosis and Malaria. This initiative aims to increase the use of artemisinin-based combination therapies for treating malaria. A pilot is underway in eight countries to determine whether the mechanism reduces the consumer price of these drugs and increases their availability in public and private outlets, their market share and their use. To evaluate the pilot, an analysis was done to estimate predetermined "benchmarks" of success at 1 and 2 years. The analysis used a mixed-methods approach, triangulating data from a literature review with information from 33 interviews with experts. A sensitivity analysis and other methods were used to verify the results. Benchmarks used to determine success include an increase in availability of artemisinin-based combination therapies of 40 percentage points from baseline, and an increase in their use of 10-15 percentage points from baseline at year 2. These benchmarks were based on evidence that national public health programmes aimed at increasing the use of a specific health commodity in developing countries have generally achieved only modest changes in use within a 2-year time frame. Evaluation should also take individual country contexts into account.